Khombouw in Science Learning: Development of Teaching Materials based on Local Wisdom Guided Inquiry Model to Improve Students' Interpersonal Skills - Bektiarso, Singgih; Walukow, Auldry F.; Narulita, Erlia; Ali, Aisyah (Pascasarjana Universitas KH. Abdul Chalim, 2024)
This research aims to develop teaching materials based on local wisdom to improve the interpersonal skills of prospective elementary school teachers. The background of this research is based on the low interpersonal skills of prospective students of Elementary School Teachers at the Faculty of Teacher Training (FKIP) Cenderawasih University (Uncen) Papua. The strategy used to improve students' interpersonal skills is to integrate Khombouw into the teaching materials of the Basic Concepts of Science Elementary School. Khombouw is a local wisdom made of bark from red khombow trees (Ficus nodosa teijsm & Binn) and white khombow (Ficus variegata Blume), which grow in Sentani, Papua. This research is a research development (R&D) of the ADDIE (Analyze, Design, Development, Implementation) design model. The results of student self-assessment on the implementation of teaching materials based on Khombouw Local Wisdom Model Guided Inquiry on interpersonal skills were 69.5% in the